The Monster in the Classroom: Assessing Language to Inform Instruction. (24th September 2019) - Goodwin, Amanda P.; Petscher, Yaacov; Jones, Sara; McFadden, Sara; Reynolds, Dan; Lantos, Tess
Abstract: The authors describe Monster, P.I., which is an app‐based, gamified assessment that measures language skills (knowledge of morphology, vocabulary, and syntax) of students in grades 5–8 and provides teachers with interpretable score reports to drive instruction that improves vocabulary, reading, and writing ability. Specifically, the authors describe why an assessment of language is important to include, the components of language that are assessed by Monster, P.I., and how Monster, P.I., uses gamification to add enjoyment and motivation to the assessment experience. The authors then explain how to use Monster, P.I., to inform instructional decisions, specifically explaining the overall instructional framework, what each score means, and examples of instruction that link to each area assessed by the app. Links to Common Core State Standards are included. The authors conclude by sharing teachers' feedback on the assessment and how they used it to support instruction in their classrooms.